Business Camp: MSME Financial Management in West Sumatra - Sanda Patrisia Komalasari; Muhammad Parkesit Wisnubroto; Kiki Yulianto (Warta Pengabdian Andalas, 2024)
Financial management is the heart of a business. Many businesses fail and eventually go bankrupt due to poor financial management. Quality products and services with sound financial management will be helpful with thorough financial planning. Empowering MSMEs is one of the government's commitments. Universities have a role in helping the government in empowering MSMEs. Therefore, Andalas University has organized various programs to carry out this role. One of the programs organized by Andalas University is the Business Camp activity. Business Camp activities consist of several types of empowerment material, including MSME financial management. First Business Camp activities with Financial Management material were conducted online using the Zoom Meeting Application. The activity was held on Saturday, 28 October 2023. The main participants in this activity were MSME owners whom Andalas University accompanied. However, this activity did not close the opportunity for other MSMEs who want to join. Therefore, as many as 80 participants had taken part in this activity. The result of this activity was the motivation for MSMEs to separate their financial books first so that sound financial management can be carried out. This activity is essential to carry out so that MSME businesses can become businesses that continue to grow.